Information Retrieval : 8th Russian Summer School, RuSSIR 2014, Nizhniy, Novgorod, Russia, August 18-22, 2014, Revised Selected Papers - Braslavski, Pavel; Karpov, Nikolay; Worring, Marcel; Volkovich, Yana.; Ignatov, Dmitry I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed proceedings of the 8th Russian Summer School on Information Retrieval, RuSSIR 2014, held in Nizhniy Novgorod, Russia, in August 2014. The volume includes 6 tutorial papers, summarizing lectures given at the event, and 8 revised papers from the school participants.The papers focus on various aspects of information retrieval. .
Document Analysis and Retrieval in Scientific Digital Libraries: Case Studies in Applying Machine Learning for Information Retrieval -- Online Experimentation for Information Retrieval -- Intoduction to Formal Concept Analysis and Its Applications in Information Retrieval and Related Fields -- Visualization and Data Mining for High Dimensional Data -- Web as Corupu: Boing Beyond the n-gram -- Author Profiling and Plagiarism Detection.
Keywords: Information storage and retrieva; Data mining; Natural language processing (Computer science).; Artificial intelligence; Database management; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Natural Language Processing (NLP).; Artificial Intelligence; Database Management